Democracy in the Middle East: An Indigenous Assessment - Mattix, Jeremiah Ian (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
During the previous century much of the world has taken great strides in adopting and implementing democracy and yet the Middle East has notably faltered. More recently with the rise of religious extremism, the region has fallen farther behind with many states retaining authoritarian forms of governance demonstrating gross humanitarian abuses. Most notably since the turn of the century, the resurgence of Islam as a driving force in regional politics, has proven a daunting challenge for the increasingly secular statesmen and academics of the West. Likewise attempts to understand the situation from an outside perspective and apply remedies concocted in western institutions have met with repeated failure and have in fact only served to bolster the anti-democratic narratives of fundamentalists and terrorists. In order to fully appreciate the roots of the dilemma and help create better communication between East and West, the people living in the Middle East need to be heard and included in the dialogue. In this study, interviews were done with a broad selection of sixteen students from the Middle East studying at the Eastern Mediterr ne n University in G zim usa, Northern Cyprus. This selection included Arabs, Turks, Iranians and Kurds from all major political and religious backgrounds. Each was asked for their thoughts on the state of democracy in the Middle East. Their answers highlight the fact that although most Middle Easterners welcome incre sed freedom they don‟t w nt the incre singly individualist democracy promoted in the West or the political and economic strings often attached to it. Their responses also underscore the essential role that Islam continues to play in the political psyche of their region, the nature of which westerners largely misunderstand. This study should prove helpful in highlighting the real concerns of the up and coming generation of Middle Easterners with a view towards fostering better understanding and communication. Keywords: Democracy, Middle East, Secularism, Human Rights, Islam, West.

ÖZ: Geçti imiz yüzyıl boyunc düny nın büyük bir kısmı demokrasiyi benimseme ve uygul m yolund büyük mes fe k t etmesine r men Ort do u bölgesi bu konuda lenen tökezlendi. Son z m nl rd yükselen şırı dinci kıml rl birlikte otokratik yönetimler v rlıkl rını dev m ettirerek büyük ins ni dr ml rın y ş nm sın sebep oldular ve bu bölgenin ülkeleri Düny Demokr si Endeksi‟nde d h d lt b s m kl r gerilediler. Özellikle 21. yüzyılın b şınd n itib ren İsl m dininin bölgesel politik l rın etkin bir gücü ol r k yeniden yükselmesi b tıd gittikçe daha f zl sekülerleşen diplomatlar ve akademisyenler için şılm sı güç bir engel haline geldi. Benzer şekilde, dış rıd n ol yı anlamaya ç lışıp, çözüm önerileri üretmek isteyen b tılı kurumlar hep b ş rısız oldular ve slınd bu sadece köktendincilerin ve teröristlerin anti-demokratik prop g nd l rını y ym l rına y rdımcı oldu. Ort do u‟d ki sorun ve ikilemlerin kökenine inmek ve B tı ile Do u r sında daha s lıklı bir iletişim s l m k için bölgede y s y n h lkl rın seslerinin daha güçlü bir şekilde duyulm sı ve diyaloga dahil edilmeleri gerekmektedir. Bu ç lışm d G zim us KKTC‟de bulun n Do u Akdeniz Üniversitesi‟nde ö renim gören Ort do u‟nun f rklı ülkelerinden on ltı ö renciye nket ç lışm sı uygul ndı. Ç lışm y f rklı dini ve politik grupl rd n Ar p Türk F rs ve Kürt ö renciler dahil edildi. Her bir k tılımcıy „Ort do u‟d ki Demokr sinin Durumu‟ h kkında sorular yöneltildi ve görüşleri lındı. Cev pl rı, her ne kadar Ort do u‟d yasayan h lkl rın ço unlu unun bireysel özgürlüklerin gelişmesini destekledi i gibi görünse de, b tılı tarzda yükselen demokr sinin ber berinde getirdi i yasam seklini ve demokrasiyle ilintili siyasi ve iktisadi modellere pek de sıc k b km dıkl rı ortaya çıktı. Ç lışm d n elde edilen bir b şk sonuçt da, İsl m dininin bölgenin siyasi psikolojisinde önemli bir rol oyn yıcı oldu u öne çıktı. Bu durum, din ve devlet işlerinin kesin çizgilerle birbirinden yrıldı ı sistemlerle yönetilen seküler B tılı yönetimlerin, İsl m dininin bölge siyasetindeki etkin rolünü anlamakta güçlük çekmelerine ve bölgeyi y nlış okum l rın sebebiyet vermektedir. Bu ç lışm , Ort do u‟d yetişmekte olan yeni nesil gençlerin güncel k ygıl rını y nsıtm kl birlikte topluml r r sınd daha s lıklı bir nl yış ve iletişim s l m kt f yd lı olm yı m çl m kt dır. Anahtar Kelimeler: Demokrasi, Ort Do u Laiklik, İns n H kl rı İslam, B tı.
Master of Arts in International Relations. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of International Relations, 2016. Supervisor: Assist. Prof. Dr. John Turner.
Keywords: Political Science and International Relations; Democracy-Middle East; Democracy; Middle East; Secularism; Human Rights; Islam; West